Sirtuins promote brain homeostasis, preventing Alzheimer’s disease through targeting neuroinflammation - Watroba, Mateusz; Szukiewicz, Dariusz (Frontiers in Physiology, 2022)
Both basic pathomechanisms underlying Alzheimer’s disease and some premises for stipulating a possible preventive role of some sirtuins, especially SIRT1 and SIRT3, protective against Alzheimer’s disease-related pathology, are discussed in this article. Sirtuins can inhibit some processes that underlie Alzheimer’s disease-related molecular pathology (e.g. neuroinflammation, neuroinflammation-related oxidative stress, Aβ aggregate deposition, and neurofibrillary tangle formation), thus preventing many of those pathologic alterations at relatively early stages of their development. Subsequently, the authors discuss in details which mechanisms of sirtuin action may prevent the development of Alzheimer’s disease, thus promoting brain homeostasis in the course of aging. In addition, a rationale for boosting sirtuin activity, both with allosteric activators and with NAD+ precursors, has been presented.